2013
DOI: 10.1002/ajim.22229
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a French series of female cases of mesothelioma

Abstract: These results will allow hypotheses to be generated about associations between mesothelioma and non-occupational asbestos exposure, X-ray exposure and history of respiratory disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…52 Studies utilizing national population databases relied on samples that were representative of the general population for a particular country or region, including both men and women (see Table 1). There are a few studies focusing on a particular population; one study focused exclusively on women, 43 one on familial MM cases, and one on those who were exposed to asbestos during childhood. 39 In addition, in a recent study of the population in Western Australia, an area with extensive research on MM related to crocidolite asbestos, Franklin et al 40 compared MM burden between non-Aboriginal and Aboriginal individuals, who comprise an understudied group.…”
Section: Data Source and Study Designmentioning
confidence: 99%
See 3 more Smart Citations
“…52 Studies utilizing national population databases relied on samples that were representative of the general population for a particular country or region, including both men and women (see Table 1). There are a few studies focusing on a particular population; one study focused exclusively on women, 43 one on familial MM cases, and one on those who were exposed to asbestos during childhood. 39 In addition, in a recent study of the population in Western Australia, an area with extensive research on MM related to crocidolite asbestos, Franklin et al 40 compared MM burden between non-Aboriginal and Aboriginal individuals, who comprise an understudied group.…”
Section: Data Source and Study Designmentioning
confidence: 99%
“…The literature classification of nonoccupational exposure to asbestos is very heterogeneous. For the purpose of this review, all nonoccupational asbestos exposure was classified as EE and further grouped into the following four categories: (1) exposure to NOA in areas where studies of the geological structure have shown the presence of asbestos but asbestos-related industries are absent; (2) neighborhood exposure based on residence in close proximity to industrial/ mining sources of asbestos; (3) household exposure for family members of occupationally exposed subjects, which includes what some authors call familial exposure 19,25 and what Camiade et al 43 and Mensi et al 28 called paraoccupational exposure, referring to those who live with an asbestos worker and those who clean asbestos-contaminated clothes; and (4) other nonoccupational exposures, which includes homerelated 28 or domestic exposure 24,41,54 (for example, Figure 2. Relative quality expressed as z scores (y axis) of the studies reviewed (x axis, in the same order as they appear in Table 1).…”
Section: Definitions Of Environmental Asbestos Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…When considering the entire dataset, for subjects occupationally 25 exposed only to asbestos between 1 to 10 fibers/ml.yrs, the OR was 3.7 [95% CI: 2.4-5.6] 26 compared to subjects not exposed to asbestos, mineral wool and silica. However, it increased to 27 additionally exposed to mineral wool, silica or to the three mineral particles respectively 29 (Lacourt et al 2013). When restricting the dataset to subjects ever exposed to asbestos (988 cases 30 and 1,125 controls), the OR for subjects occupationally exposed only to asbestos at 50 fibers/ml-31 yrs was 1.9 [95% CI: 1.4-2.5] and was 12.8 [95% CI: 4.7-35.1] when subjects were additionally 1 exposed to refractory ceramic fibers (Lacourt et al 2014).…”
Section: Mesothelioma 2mentioning
confidence: 98%